The Influence of Corporate Image, Price Perception, Service Quality, and Electrifying Lifestyle on Consumer Loyalty Towards Electric Vehicles with Consumer Satisfaction as an Intervening Variable (An Environmental Study of PT PLN UID Banten for the 2021–2024 Period) - Fajarwati, Elliza; Tjahjaningsih, Endang (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The study was conducted to investigate the effects of corporate image, price perception, service quality, and electrifying lifestyle on consumer loyalty, with consumer satisfaction being used as a mediating variable among electric vehicle users at PT PLN UID Banten from 2021 to 2024. A quantitative method was employed, and primary data were obtained through questionnaires distributed to 100 respondents using a non-probability sampling technique. The data were analyzed through multiple linear regression, and the mediation effect was tested using the Sobel test. It was found that service quality and electrifying lifestyle were positively and significantly associated with consumer satisfaction, while corporate image and price perception were not found to have significant effects. Consumer loyalty was positively influenced by price perception, service quality, electrifying lifestyle, and consumer satisfaction, whereas no direct effect was observed from corporate image. The mediation effect of consumer satisfaction was confirmed in the relationships involving price perception, service quality, and electrifying lifestyle, but not in the relationship involving corporate image.